The New Regulation in the Romanian Law Concerning the Victim’s Consent – a Case which Exonerates from Liability - Jugastru, Călina (Wydział Prawa i Administracji Uniwersytetu Rzeszowskiego, 2013)
The problem of the victim’s consent, requires a differentiated analysis, as it regards the damage caused to the goods, the damage caused through violations of the right to life, health or physical integrity or the damage resulted from the breach of some non-patrimonial rights, other than the right to life, health, integrity. Where consent allows the diminution or exoneration from liability, it will be verified under the aspect of meeting the conditions requested by law for its validity. The rule is the interdiction to cause injury to the human body. The human body is inviolable and indispensable. Generally, no disclaimer can regard this type of rights which are granted and protected by the norms of the positive law. The human body is indispensable, which means that neither the body, as a whole, nor its elements, can form the object of transaction. All the situations of exception are strictly subordinated to the condition of the prior consent of the victim. She does not consent to the occurrence of the damage, but manifests her agreement to the performance of that activity – activity that also presents the risk of generating certain damages. The problem of the consent has special connotations within the medical field, especially in relation to the aesthetic surgery; when patients are incapable of expressing their consent; in the case of drawing of tissues, organs or human cells; in the framework of bioethics activities. Moreover, the consent is a prior and indispensable condition for the disclosure of personal rights. In the Romanian legal system, the principle of consent was regulated for the first time in the new Civil code. It governs the entire field of personal rights. It is expressly stipulated in relation to the private life, right to dignity, right to one’s own image, to the respect owed to the deceased person.

Problem zgody ofiary wymaga zróżnicowanej analizy, gdyż dotyczy on szkód wyrządzonych przedmiotom, szkód spowodowanych poprzez pogwałcenie prawa do życia, zdrowia lub nienaruszalności cielesnej, czy też szkód spowodowanych przez naruszenie niektórych praw niemajątkowych, innych niż prawo do życia, zdrowia i nienaruszalności. W przypadkach, w których zgoda pozwala na ograniczenie lub uniknięcie odpowiedzialności, będzie ona badana pod względem spełnienia warunków dla jej ważności wymaganych przez prawo. Regułą jest zakaz powodowania uszkodzenia ludzkiego ciała. Ludzkie ciało jest nietykalne i niezastąpione. W zasadie nie można zrzec się takiego prawa, które jest nadawane i chronione przez normy prawa stanowionego. Ciało ludzkie jest niezastąpione, co oznacza, że ani ciało, jako całość, ani żadna jego część nie mogą stanowić przedmiotu transakcji. Wszystkie te przypadki wyjątkowe są ściśle podporządkowane warunkowi uprzedniej zgody ofiary. Nie wyraża ona zgody na uszkodzenia ciała, lecz deklaruje zgodę na wykonanie czynności, która również niesie ryzyko spowodowania pewnych szkód. Problem zgody ma szczególne znaczenie w dziedzinie medycyny, zwłaszcza w chirurgii estetycznej, kiedy pacjenci nie są zdolni do wyrazenia zgody, w przypadku pobierania tkanek, organów oraz komórek ludzkich, a także w działaniach o charakterze bioetycznym. Co więcej, zgoda jest wcześniejszym i niezbędnym warunkiem dla ujawnienia praw osobistych. W rumuńskim systemie prawnym zasada udzielenia zgody po raz pierwszy została uregulowana w nowym kodeksie cywilnym. Rządzi on całą dziedziną praw osobistych. Ma zastosowanie w związku z życiem prywatnym, prawem do godności, prawem do własnego wizerunku oraz szacunku dla osoby zmarłej.
Nowa regulacja w prawie rumuńskim dotycząca zgody ofiary – przypadku, który uwalnia od odpowiedzialności
Keywords: civil liability; odpowiedzialność cywilna; new Romanian Civil code; justificatory cases; justificatory cases; victim’s consent; damage caused to the goods; damages caused to the physical or mental integrity; nowy rumuński kodeks cywilny; usprawiedliwiające przypadki; szkoda wyrządzona przedmiotom; zgoda ofiary; szkody na nienaruszalności cielesnej i umysłowej